Implementation Of The Basic Concept Of Corporate Social Responsibility As A Branding Strategy at Amboina Restaurant - Dita Arisona; Muh Syarif; Nurita Andiani (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
Companies carry out their social responsibility in various forms and each company implements CSR in several ways. This restaurant produces heavy food such as mixed rice, soto, rawon, and egg petis. The uniqueness of this restaurant is that when producing food, it has a unique taste image, namely with the typical spices of Bangkalan Regency which is rich in spices, besides that it is no less interesting with large pieces of fish compared to the others, with its uniqueness this Amboina restaurant applies one of the following: One CSR triple bottom line is people, so the researcher proposes to apply all triple bottom lines with the aim of obtaining a positive image in the hope of having a long product life cycle. This research is a qualitative type with an interview method that obtains the results of this study, namely the proposal of triple bottom line people in the form of social action, performance innovation, and employee rewards. Planet with training in reducing household waste that is used as fertilizer and liquid soap. Profit in the form of CSR regarding financial science to be more specific in processing finances.